Sudden cardiac death in young athletes - Östman-Smith, I. (Open Access Journal of Sports Medicine, 2011)
Athletic activity is associated with an increased risk of sudden death for individuals with some congenital or acquired heart disorders. This review considers in particular the causes of death affecting athletes below 35 years of age. In this age group the largest proportion of deaths are caused by diseases with autosomal dominant inheritance such as hypertrophic cardiomyopathy, arrhythmogenic right ventricular cardiomyopathy, long QT-syndrome, and Marfan`s syndrome. A policy of early cascade-screening of all first-degree relatives of patients with these disorders will therefore detect a substantial number of individuals at risk. A strictly regulated system with preparticipation screening of all athletes following a protocol pioneered in Italy, including school-age children, can also detect cases caused by sporadic new mutations and has been shown to reduce excess mortality among athletes substantially. Recommendations for screening procedure are reviewed. It is concluded that ECG screening ought to be part of preparticipation screening, but using criteria that do not cause too many false positives among athletes. One such suggested protocol will show positive in approximately 5% of screened individuals, among whom many will be screened for these diseases. On this point further research is needed to define what kind of false-positive and false-negative rate these new criteria result in. A less formal system based on cascade-screening of relatives, education of coaches about suspicious symptoms, and preparticipation questionnaires used by athletic clubs, has been associated over time with a sizeable reduction in sudden cardiac deaths among Swedish athletes, and thus appears to be worth implementing even for junior athletes not recommended for formal preparticipation screening. It is strongly argued that in families with autosomal dominant disorders the first screening of children should be carried out no later than 6 to 7 years of age.